A novel panel of yeast assays for the assessment of thiamin and its biosynthetic intermediates in plant tissues. Issue 2 (8th February 2022) - Strobbe, Simon; Verstraete, Jana; Fitzpatrick, Teresa B.; Faustino, Maria; Lourenço, Tiago F.; Oliveira, M. Margarida; Stove, Christophe; Van Der Straeten, Dominique
Summary: Thiamin (or thiamine), known as vitamin B1, represents an indispensable component of human diets, being pivotal in energy metabolism. Thiamin research depends on adequate vitamin quantification in plant tissues. A recently developed quantitative liquid chromatography–tandem mass spectrometry (LC–MS/MS) method is able to assess the level of thiamin, its phosphorylated entities and its biosynthetic intermediates in the model plant Arabidopsis thaliana, as well as in rice. However, their implementation requires expensive equipment and substantial technical expertise. Microbiological assays can be useful in deter‐mining metabolite levels in plant material and provide an affordable alternative to MS‐based analysis. Here, we evaluate, by comparison to the LC–MS/MS reference method, the potential of a carefully chosen panel of yeast assays to estimate levels of total vitamin B1, as well as its biosynthetic intermediates pyrimidine and thiazole in Arabidopsis samples. The examined panel of Saccharomyces cerevisiae mutants was, when implemented in microbiological assays, capable of correctly assigning a series of wild‐type and thiamin biofortified Arabidopsis plant samples. The assays provide a readily applicable method allowing rapid screening of vitamin B1 (and its biosynthetic intermediates) content in plant material, which is particularly useful in metabolic engineering approaches and in germplasm screening across or within species.